A review of public health guidelines for postpartum physical activity and sedentary behavior from around the world - Kelly R. Evenson; Wendy J. Brown; Alison K. Brinson; Emily Budzynski-Seymour; Melanie Hayman (Elsevier, 2024)
Background: The period following pregnancy is a critical time window when future habits with respect to physical activity (PA) and sedentary behavior (SB) are established; therefore, it warrants guidance. The purpose of this scoping review was to summarize public health-oriented country-specific postpartum PA and SB guidelines worldwide. Methods: To identify guidelines published since 2010, we performed a (a) systematic search of 4 databases (CINAHL, Global Health, PubMed, and SPORTDiscus), (b) structured repeatable web-based search separately for 194 countries, and (c) separate web-based search. Only the most recent guideline was included for each country. Results: We identified 22 countries with public health-oriented postpartum guidelines for PA and 11 countries with SB guidelines. The continents with guidelines included Europe (n = 12), Asia (n = 5), Oceania (n = 2), Africa (n = 1), North America (n = 1), and South America (n = 1). The most common benefits recorded for PA included weight control/management (n = 10), reducing the risk of postpartum depression or depressive symptoms (n = 9), and improving mood/well-being (n = 8). Postpartum guidelines specified exercises to engage in, including pelvic floor exercises (n = 17); muscle strengthening, weight training, or resistance exercises (n = 13); aerobics/general aerobic activity (n = 13); walking (n = 11); cycling (n = 9); and swimming (n = 9). Eleven guidelines remarked on the interaction between PA and breastfeeding; several guidelines stated that PA did not impact breast milk quantity (n = 7), breast milk quality (n = 6), or infant growth (n = 3). For SB, suggestions included limiting long-term sitting and interrupting sitting with PA. Conclusion: Country-specific postpartum guidelines for PA and SB can help promote healthy behaviors using a culturally appropriate context while providing specific guidance to public health practitioners.